Selective Inhibitors of Human Neutrophil Proteinase 3 - Korkmaz, Brice; Kellenberger, Christine; Viaud-Massuard, Marie-Claude; Gauthier, Francis (Current Pharmaceutical Design, 2013)
Human neutrophil proteinase 3 (PR3) and elastase (HNE) are homologous serine proteinases involved in the proteolytic events associated with inflammation and infection. Their close structural and functional resemblance makes it difficult to understand their respective biological functions. Thus, all natural inhibitors of PR3 identified to date preferentially target HNE, and only recently have inhibitors that target PR3 selectively been described. This review describes how differences in the structures of the extended active sites of PR3 and HNE can be exploited to produce selective inhibitors of PR3.
Keywords: neutrophil